Konsep Problem Solving dalam Al-Qur’an: Analisis Tematik atas Ayat-Ayat Pemecahan Masalah - Mahdini Mahdini; Ajahari Ajahari (Jurnal Pendidikan Tambusai, 2025)
This study is motivated by the growing complexity of social problems and the need for solutions rooted systematically in Qur’anic teachings. The purpose is to analyze the problem solving concept in the Qur’an thematically, focusing on QS. Asy-Syūrā: 38, QS. Al-Ḥasyr: 18, and QS. Asy-Syarḥ: 5-6 as foundations for collective, strategic, and spiritual problem solving. This qualitative study employs a library research method. The population includes all Qur’anic verses related to problem solving, with purposive sampling of the three primary surahs. Data was collected through documentation of tafsir literature and scientific journals, then thematically analyzed via content analysis with triangulation validation. Findings reveal that consultation fosters objective collective decision-making; planning and self-evaluation serve as strategic bases for problem anticipation; meanwhile, optimism and reliance on God provide spiritual strength for psychological resilience. In conclusion, these three concepts form a comprehensive and applicable Qur’anic framework for problem solving in contemporary contexts. The study recommends developing education and social practices based on these values for sustainable social solutions.